A Comparative Study: The Use of Collagen Implant versus Mitomycin-C in Combined Trabeculotomy and Trabeculectomy for Treatment of Primary Congenital Glaucoma - Alaa Abdel Sadek Singab; Osama Ali Mohammed; Mohammed Iqbal Hafez Saleem; Mortada Ahmed Abozaid (Journal of Ophthalmology)
Purpose. To compare Ologen implant versus mitomycin-C (MMC) in combined trabeculotomy and trabeculectomy as a treatment of primary congenital glaucoma. Setting. Sohag University Hospital, Egypt. Design. A prospective comparative study. Methods. Thirty-four eyes of twenty-one patients with primary congenital glaucoma were included in this study. All patients were subjected to preoperative evaluation including complete anterior segment examination under general anesthesia. The patients were divided into two groups: patients of the first group (group A) underwent combined trabeculotomy and trabeculectomy with Ologen implantation while those of the second group (group B) underwent combined trabeculotomy and trabeculectomy with MMC application. Results. Postoperatively, the IOP in group A was as follows: 8 eyes developed IOP levels less than 14 mmHg (complete success), 3 eyes had levels between 14 and 16 mmHg (accepted result), 2 eyes had levels between 16 and 20 mmHg (guarded result), and only 2 eyes showed levels exceeding 20 mmHg (failed procedure), while in group B, 7 eyes showed complete success, 3 eyes had accepted result, 3 eyes had guarded result, and 2 eyes had failed procedure. Conclusion. Ologen is a safe and effective adjuvant in combined trabeculotomy and trabeculectomy for treatment of primary congenital glaucoma.